AB0473 Quality of Life in Patients with Systemic Lupus Erythematosus and Rheumatoid Arthritis Measured by The SF36. (15th July 2016) - Acosta Colman, M.I.; Roman, L.; Cabrera, S.; Avila Pedretti, G.; Acosta Colman, M.E.; Rojas, E.; Yinde, Y.; Losanto, J.; Duarte, M.
Abstract : Background: Systemic Lupus Erythematosus (SLE) and rheumatoid arthritis (RA) are autoimmune diseases that mainly affect people in the reproductive stage of their life; it is interesting to investigate the impact of both diseases have in patient's quality of life. Objectives: The main objective of this study was to evaluate the quality of life of patients diagnosed with SLE and RA using the SF36 questionnaire and the factors that influence it Methods: Analytical, observational cross-sectional study of a cohort of SLE and RA patients. A large number of clinical and epidemiological variables were recorded (i.e. years of evolution, the age at diagnosis, disease activity, gender, marital status, etc). Quality of life was determined by SF36 questionnaire. Statistical analysis was performed with SPSS19.0 program. Qualitative variables were expressed as percentages and frequencies while quantitative were informed as mean and standard deviation. Association was analyzed with X2 test and Student T test. Pearson's test was used for correlation analysis. Results: 112 patients were studied, 50.9% (57/112) patients had SLE and 49.1% (55/112) RA. 69.6% (78/112) of patients came from the capital city and metropolitan area. 87.5% (90/112) were female, 57.14% (64/112) were living in couple and 49.1% (55/100) had basic education. 43.8% (49/97) perceive less or equal to the minimum wage monthly income. 42% (47/98) were living with 3 or fewer inhabitants in the house and 58.9% (66/108) had ≥40 years old at disease onset. The mean value of physical (PCS) component of SF36 questionnaire in SLE and RA was 45.13±12.5 and 47.7±12.5 respectively and the difference between them was significantly (p=0.01). On the other hand, the mean value of mental (MCS) component was 47.7±12.5 and 46.4±12 respectively but no significant difference was found (p=0.58). In relation to the 8 SF36 components we found significant difference between them, principally in the components that measures body pain (p=0.0001) and health perception (p=0.047). In SLE patients, a significant negative correlation it was found between PCS and HAQ (p=0.00018) and SLEDAI (p=0.0020). No significantly correlation with MCS was found. Regarding the SLICC Score, a statistically negative correlation was found with MCS (p=0.036). In RA patients, a significant negative correlation was found between PCS and HAQ (p=0.0001), no association with the DAS28 was found. But, a negative correlation between the MCS and DAS28 (p=0.03) was found. No significant correlation was observed with HAQ. Conclusions: In this cohort revealed that physical and mental component of SF36 are influenced by the disease activity and functional impairment. Acknowledgement: Sr Horacio Medina Disclosure of Interest: None declared